2020
DOI: 10.1021/acs.energyfuels.0c00720
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cigarette Carbonaceous Hydrochar/ZIF-67-Based Fluids for CO2 Capture from a Gas Stream in a Packed Column: Mass-Transfer Performance Evaluation

Abstract: The present study is focused on green technology for converting cigarette filters (CFs) into cigarette carbonaceous (CC) hydrochar as a useful product with added value and lower toxicity. This work was aimed at three primary environmental goals: first, the valorization of CFs by their conversion into a novel adsorbent as a cheap and economic source; second, this structure can offer highly stable and reactive support for growing ZIF-67 metal–organic framework (MOF); and third, the CC-hydrochar/ZIF-67 nanofluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Then, the researchers assess the mass-transfer performance in the applied absorbents via computing the overall mass-transfer coefficient in each unit volume (KGa), the number of transfer units (NTU), the total height of packing in the column (Z), and the height of transfer unit (HTU). Finally, they propose CC-hydrochar-ZIF-67 nano-fluid as an effective and affordable alternative to conventional absorbents [124].…”
Section: Adsorption In Aqueous Solutionmentioning
confidence: 99%
“…Then, the researchers assess the mass-transfer performance in the applied absorbents via computing the overall mass-transfer coefficient in each unit volume (KGa), the number of transfer units (NTU), the total height of packing in the column (Z), and the height of transfer unit (HTU). Finally, they propose CC-hydrochar-ZIF-67 nano-fluid as an effective and affordable alternative to conventional absorbents [124].…”
Section: Adsorption In Aqueous Solutionmentioning
confidence: 99%
“…188 Jaberi et al utilized cigarette filters as the carbon source to generate cigarette carbon; the ZIF-67 was then grown on the cigarette carbon to form a composite adsorbent (CC-ZIF-67). 189 The prepared CC-ZIF-67 nanofluid passed through the packed bed column at a fixed liquid flow rate to increase the interface area between adsorbent and CO 2 . The adsorption experiments on the packed bed column indicated that a faster gas flow rate and liquid flow rate are not conducive to CO 2 capture.…”
Section: ■ Co 2 Separationmentioning
confidence: 99%
“…and deformation vibration (C–H bond, O–H bond, N–H bond, etc.) in the frameworks . It should be noted that free water, associated water, and X–H groups (X presents C/N/O element, e.g., −CH 3 , N–H, C–H, etc.)…”
Section: Results and Discussionmentioning
confidence: 99%
“…in the frameworks. 53 It should be noted that free water, associated water, and X−H groups (X presents C/N/O element, e.g., −CH 3 , N−H, C−H, etc.) in the frameworks were obviously removed after pyrolysis.…”
Section: Methodsmentioning
confidence: 99%